Problematizations of Individualism in Latin America [Problematizaciones del Individualismo en América Latina] - Araujo-Kakiuchi, K (Flacso Mexico, 2020)
This paper addresses the question of why, despite a widespread recognition of the existence of an important set of individualistic manifestations in Latin America, there is a strong reluctance in these societies to interpret themselves from the framework of individualism. It argues that understanding this paradox demands to take into account the vicissitudes of the tension between a specific process of individuation (agentic individuation) and a political and juridical individualism in its liberal version. To develop this argument five major problematizations are established and discussed. © 2020 Flacso Mexico. All rights reserved.